Development of annual urban heat island in Baghdad under climate change - Wahab, Basim I.; Naif, Salwa S.; Al-Jiboori, Monim H. (Journal of Environmental Engineering and Landscape Management, 2022)
This study investigated the confirmation of climate change by analyzing the long-term records of annual means of temperature taken from synoptic station located at International Baghdad Airport (rural site) available for the period from 1978 to 2019. Furthermore, based on annual temperature data recorded by automatic weather station installed at Mustansiriyah University (urban station), available for the period 2008–2019, the difference between urban and rural temperatures called as urban heat island (UHI) intensity was annually calculated. Statistic descriptive methods including temperature trend, percentile function and R-square were employed to recognize the contribution of UHI in enhancing the local warming climate. The results show that there was a warming trend of 0.052 °C/year for period of 42 years and 0.02 °C/year for recent 12 years at rural station which is lower than 0.13 °C/year observed at urban station. Also the results for annual UHI were found to be always positive intensity which ranges from 0.8 to 2.4 °C with a mean value of 1.78 °C. As a result of high annual UHI intensity, hot day events during 2008–2019 were extracted from daily temperatures exceeding of threshold value of 37.5 °C that dominate in summer months with totally 204 events and with an annual average of 17 days. Finally, under the continuing local warming climate, potential effects caused by UHI and its mitigation strategies are further presented.